2D negative capacitance field-effect transistor with organic ferroelectrics. (16th April 2018) - Zhang, Heng; Chen, Yan; Ding, Shijin; Wang, Jianlu; Bao, Wenzhong; Zhang, David Wei; Zhou, Peng
Abstract: In the past fifty years, complementary metal-oxide-semiconductor integrated circuits have undergone significant development, but Moore's law will soon come to an end. In order to break through the physical limit of Moore's law, 2D materials have been widely used in many electronic devices because of their high mobility and excellent mechanical flexibility. And the emergence of a negative capacitance field-effect transistor (NCFET) could not only break the thermal limit of conventional devices, but reduce the operating voltage and power consumption. This paper demonstrates a 2D NCFET that treats molybdenum disulfide as a channel material and organic P(VDF-TrFE) as a gate dielectric directly. This represents a new attempt to prepare NCFETs and produce flexible electronic devices. It exhibits a 10^6 on-/off-current ratio. And the minimum subthreshold swing (SS) of the 21 mV/decade and average SS of the 44 mV/decade in four orders of magnitude of drain current can also be observed at room temperature of 300 K.